The feasibility and accuracy of using a remote method to assess computer workstations. - Baker, Nancy A; Jacobs, Karen (Human Factors, 2014)
Objective: The objective was to test the accuracy of using remote methods (tele-ergonomics) to identify potential mismatches between workers and their computer workstations.Background: Remote access to ergonomic assessments and interventions using two-way interactive communications, tele-ergonomics, increases the ability to deliver computer ergonomic services. However, this mode of delivery must first be tested for accuracy.Method: In this single group study, the computer workstations of 30 participants who reported mild to moderate discomfort were remotely assessed using photographs taken by a research assistant and the self-report Computer Workstation Checklist (CWC) completed by the study participant. Mismatches identified remotely by an ergonomics expert were compared to results obtained from an onsite computer workstation visit completed by the same expert.Results: We accurately identified 92% of mismatches. The method was more sensitive (0.97) than specific (0.88), indicating that experts using the remote method were likely to overidentify mismatches.Conclusion: These results suggest that an expert using the self-reported CWC combined with workstation photographs can accurately identify mismatches between workers and their computer workstations.Application: Remote assessment is a promising method to improve access to computer workstation ergonomic assessments.